Current Status of Childhood Obesity and its Associated Morbidities in Turkey - BEREKET, ABDULLAH (GALENOS YAYINCILIK, 2012)
As a transitional society, rapid changes have occurred in the social, economic, nutritional and lifestyle aspects of the Turkish population over the last three decades. As a result, the prevalence of overweight and obesity has shown a dramatic increase in the adult Turkish population, reaching figures as high as 30-40%. Although there is no nationwide figure regarding the prevalence of overweight and obesity in Turkish children and adolescents, several local studies performed between 2000 and 2010 in different regions of the country have demonstrated varying prevalence rates of 10.3%-17.6% and 1.9%-7.8% for overweight and obesity, respectively, in children aged 6-16 years. The differences in the figures obtained in these regions are thought to be due to variations in the subject sampling. The figures appear to vary depending on residential (urban vs. rural) and economic conditions. Belonging to a high-income family, living in a large city, having obese parents, being of high birthweight, consuming sugar-sweetened beverages (soft drinks, juice drinks, etc.), and spending time in front of TV and PC were identified as the most common risk factors. Complications and co-morbidities of obesity have also started to appear in our pediatric population. Metabolic syndrome, diagnosed according to the International Diabetes Federation criteria, was found in 2.3% of Turkish schoolchildren aged 10-19 years. This rate was 28% in obese children. Preventive public measures have started to be implemented by the State and other bodies to control the rising trends in obesity.
Keywords: Childhood; obesity; current status; METABOLIC SYNDROME; TURKISH CHILDREN; SCHOOL-CHILDREN; RISK-FACTORS; FATTY LIVER; PREVALENCE; ADOLESCENTS; OVERWEIGHT; MENARCHE; TISSUE